2004
DOI: 10.1530/rep.1.00244
|View full text |Cite
|
Sign up to set email alerts
|

Spermatozoa motility in the Persian sturgeon, Acipenser persicus: effects of pH, dilution rate, ions and osmolality

Abstract: Sperm motility is a prerequisite factor determining semen quality and fertilizing capacity. The effects of environmental factors including pH, cations and osmolality as well as the role of dilution rate on sperm motility parameters in Acipenser persicus were studied. The best pH and dilution rate for activation of spermatozoa were pH 8.0 and dilution ratio 1:50. Ionic factors can stimulate the initiation of sperm activation. The maximum percentage of motile sperm and total duration of sperm motility were obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 42 publications
5
55
2
Order By: Relevance
“…In fish, several factors have been reported that regulate the composition of seminal plasma (Ciereszko, 2008;Alavi et al, 2008b). It has already been shown in the literature that there are several correlations between seminal plasma composition and sperm motility in some species: Salmo salar (Hwang and Idler, 1969), Cyprinus carpio (Kruger et al, 1984), rainbow trout (Lahnsteiner et al, 1998), Persian sturgeon, Acipenser persicus (Alavi et al, 2004), and Oncorhynchus tshawytscha (Rosengrave et al, 2009). Lahnsteiner et al (1996) reported a correlation between sperm motility and seminal plasma composition in bleak Alburnus alburnus, a cyprinid, and suggested that this correlation might indicate which components of the seminal plasma influence sperm motility.…”
Section: Discussionmentioning
confidence: 99%
“…In fish, several factors have been reported that regulate the composition of seminal plasma (Ciereszko, 2008;Alavi et al, 2008b). It has already been shown in the literature that there are several correlations between seminal plasma composition and sperm motility in some species: Salmo salar (Hwang and Idler, 1969), Cyprinus carpio (Kruger et al, 1984), rainbow trout (Lahnsteiner et al, 1998), Persian sturgeon, Acipenser persicus (Alavi et al, 2004), and Oncorhynchus tshawytscha (Rosengrave et al, 2009). Lahnsteiner et al (1996) reported a correlation between sperm motility and seminal plasma composition in bleak Alburnus alburnus, a cyprinid, and suggested that this correlation might indicate which components of the seminal plasma influence sperm motility.…”
Section: Discussionmentioning
confidence: 99%
“…The pH of the activation medium has been identified as a major factor affecting the motility and velocity of fish sperm (Stoss 1983;Alavi and Cosson 2005), which subsequently influences sperm fertility (Billard et al 1995;Linhart et al 2006). In sturgeon, the optimal pH for sperm motility has been reported as pH 8-9 (Gallis et al 1991;Cosson and Linhart 1996;Ingermann et al 2002;Alavi et al 2004). In white sturgeon, A. transmontanus, sperm pre-incubated at pH 8.2 or higher showed higher motility following transfer into water as a swimming medium, but motility decreased or ceased when sperm were pre-incubated at pH 7.5 or lower (Ingermann et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Several published studies have analysed sperm quality and its relationship to reproductive success in a variety of sturgeon species, such as paddlefish, Polyodon spathula Cosson and Linhart 1996); white sturgeon, Acipenser transmontanus (Ingermann et al 2002); Siberian sturgeon, A. baeri (Gallis et al 1991); and Persian sturgeon, A. persicus (Alavi et al 2004;Aramli et al 2013a;Dadras et al 2014). Unfortunately, data concerning the biological aspects of sperm and their fertility in…”
mentioning
confidence: 99%
“…Motility of salmonid sperm is sensitive to very low concentrations of K + (more than 1 mM) (28), which are lower than levels for sturgeon sperm (more than 2 mM) (29). K + can control activation in sturgeon sperm at very low concentrations (0.01-0.3 mM) in A. baeri, A. persicus, P. spathula, and A. fulvescens sperm (12,13).…”
Section: +mentioning
confidence: 99%